2012
DOI: 10.1523/jneurosci.6489-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal Contributions to Metacognition in Perceptual Decision Making

Abstract: Neuroscience has made considerable progress in understanding the neural substrates supporting cognitive performance in a number of domains, including memory, perception, and decision making. In contrast, how the human brain generates metacognitive awareness of task performance remains unclear. Here, we address this question by asking participants to perform perceptual decisions while providing concurrent metacognitive reports during fMRI scanning. We show that activity in right rostrolateral prefrontal cortex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

52
323
6
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 353 publications
(382 citation statements)
references
References 62 publications
52
323
6
1
Order By: Relevance
“…More generally, our work on functional brain networks and Garfinkel et al's behavioral studies (34), are only the first steps to understanding what may be a complex pattern of interactions between the systems of metacognitive ability and interoception. This may help bridge the fertile but largely disconnected literature of metacognitive ability (2,(35)(36)(37) and interoception (17,32,33,38).…”
Section: Discussionmentioning
confidence: 95%
“…More generally, our work on functional brain networks and Garfinkel et al's behavioral studies (34), are only the first steps to understanding what may be a complex pattern of interactions between the systems of metacognitive ability and interoception. This may help bridge the fertile but largely disconnected literature of metacognitive ability (2,(35)(36)(37) and interoception (17,32,33,38).…”
Section: Discussionmentioning
confidence: 95%
“…Trials that strongly involved manipulation of WM content were characterized by a decrease in metacognition. Not surprisingly, metacognition also is associated with activation in prefrontal areas (Fleming, Huijgen, & Dolan, 2012). Taken together, it cannot be determined whether increased demands on executive WM truly affect the threshold for visual awareness or merely influence subsequent stages such as deciding on a response or assessing the metacognitive quality of the visual awareness.…”
Section: Discussionmentioning
confidence: 98%
“…A number of recent studies have identified the neural correlates of confidence in perceptual and economic decision-making (44,45). Importantly, these studies focused on single participants, leaving open the possibility that confidence as communicated in social interaction may have a different set of neural correlates, or, at least, involve other stages of processing (46).…”
Section: Discussionmentioning
confidence: 99%